مفهوم عقد الأشتراك في شبكة الأنترنت وتكييفه القانوني دراسة تحليلية - حسين, زبير مصطفى; محمدأمين, رزكار عبدول (Sulaimani Journal for Humanities, 2021)
This study deals with one of the important contemporary legal issues related to a vital area of the individual and society's life, which requires studying the legal rules regulating this topic in a way that provides legal protection for the participants who are the weak party position in the legal relationship under study. It includes the definition of the Internet subscription contract, its characteristics and the elements of its formation, in addition to specifying its legal adaptation, whether it is a contract for leasing Internet services, or a contract for the sale of those services, or a contract that responds to internet services? Provided that creating legal problems needs legal treatment which was the goal of this study. At the end, it becomes evident that the Internet subscription contract is close to a contract for the Internet services. However, we recommend that the Iraqi legislator enact legislation for this contract.